Ze lo kaχa ‘It’s Not Like That’: The Functions of the discourse-deictic kaχa ‘thus’ in spoken Israeli Hebrew - Shor, Leon (Studia Orientalia Electronica, 2017)
The lexeme kaχa ‘thus’, ‘in this manner’ serves as the primary manner demonstrative in informal Israeli Hebrew. In its basic exophoric function, kaχa may be used by the speaker to refer to some visible physical behavior or state of affairs in the speech situation; much more frequently, however, kaχa is employed by the interlocutor’s discourse deictically, targeting existing or anticipated discourse segments, originating either in the speaker’s own speech or in the speech of any of the interlocutors. This study analyzes the functional distribution of the discourse-deictic kaχa in spoken Israeli Hebrew, attempting to characterize its possible referents and to identify the pragmatic actions performed by the entire utterance in which kaχa is embedded. The results show that as a discourse-deictic manner demonstrative, kaχa points – retrospectively or prospectively – to an extended discourse segment which spans either a single utterance or several utterances. This discourse segment typically contains a claim, an opinion or an assessment expressed by one of the interlocutors. In so doing, kaχa, together with the entire utterance in which it is embedded, serves different pragmatic purposes. Retrospective kaχa utterances typically have an evaluative function – they are used by the next speaker to respond to the prior speaker’s stance with regard to some state of affairs, resulting in convergent or divergent alignment with that speaker. Prospective kaχa utterances, on the other hand, were found to preface the speaker’s upcoming extended turns, functioning as a “floor-claiming” device that draws the recipient’s attention to the upcoming turn and heightens his interest in its expected content.